Effectiveness of telerehabilitation on the International Classification of Functioning, Disability, and Health framework outcomes during the COVID-19 pandemic: A systematic review and meta-analysis of randomized controlled trials - Jenjira Thanakamchokchai; Fuengfa Khobkhun; Ruttana Phetsitong; Pakaratee Chaiyawat; Kantheera Areerak; Kanjana Niemrungruang; Jarugool Tretriluxana (Digital Health)
Objective This study aimed to synthesize and analyze the evidence on the effectiveness of telerehabilitation categorized according to the International Classification of Functioning, Disability, and Health (ICF) outcomes for physical therapy (PT) during the coronavirus disease 2019 (COVID-19) pandemic. Methods Studies were identified using the Physiotherapy Evidence Database (PEDro), Scopus, PubMed, EMBASE, and other sources of data. Randomized controlled trials comparing telerehabilitation with the control group (i.e., no treatment/usual care) were included. Standard meta-analysis techniques were applied to assess the effectiveness of telerehabilitation. Outcome measures were categorized according to the domains of the ICF. Results Among the 134 studies that met the eligibility criteria, the majority of findings demonstrated significant improvements across all domains of the ICF following telerehabilitation as compared to the control group, regardless of participant groups. Only 9 of 134 studies were included in the meta-analysis. Six studies enrolled individuals with COVID-19 and the remaining three enrolled individuals with knee osteoarthritis (OA) who were unable to access services at the clinic. Compared with the control group, the Borg-Rating-of-Perceived-Exertion scale, as reflected in an impairment domain, was significantly lower in individuals with COVID-19 who received telerehabilitation (3 studies, n  = 135; standardized mean difference (SMD) −1.82, 95% CI −2.77 to −0.86). Compared with that in the control group, 30-second sit-to-stand test (3 studies, n  = 122; SMD 0.88, 95% CI 0.52–1.25) and 6-minute-walking test (4 studies, n  = 221; SMD 0.83, 95% CI 0.42–1.24), as reflected to an activity domain, showed significant improvement in the telerehabilitation group. Conversely, there was no effectiveness of telerehabilitation on an activity domain as measured by the timed up and go test in people with knee OA (3 studies, n  = 111; SMD −0.45, 95% CI −1.19 to 0.30). Conclusion This study provides evidence supporting the effectiveness of telerehabilitation across all domains of the ICF, with significant improvements observed in the impairment and activity domains for individuals with COVID-19. These improvements are particularly evident in the meta-analysis findings such as perceived exertion, leg strength, and functional capacity.